# Solve for x -6/5x=-5 -65x=-5
Multiply both sides of the equation by -56.
-56⋅(-65)⋅x=-56⋅-5
Simplify both sides of the equation.
Simplify -56⋅(-65)⋅x.
Cancel the common factor of 5.
Move the leading negative in -56 into the numerator.
-56⋅(-65)⋅x=-56⋅-5
Move the leading negative in -65 into the numerator.
-56⋅-65⋅x=-56⋅-5
Factor 5 out of -5.
5(-1)6⋅-65⋅x=-56⋅-5
Cancel the common factor.
5⋅-16⋅-65⋅x=-56⋅-5
Rewrite the expression.
-16⋅-6⋅x=-56⋅-5
-16⋅-6⋅x=-56⋅-5
Cancel the common factor of 6.
Factor 6 out of -6.
-16⋅(6(-1))⋅x=-56⋅-5
Cancel the common factor.
-16⋅(6⋅-1)⋅x=-56⋅-5
Rewrite the expression.
-1⋅-1⋅x=-56⋅-5
-1⋅-1⋅x=-56⋅-5
Multiply.
Multiply -1 by -1.
1⋅x=-56⋅-5
Multiply x by 1.
x=-56⋅-5
x=-56⋅-5
x=-56⋅-5
Multiply -56⋅-5.
Multiply -5 by -1.
x=5(56)
Combine 5 and 56.
x=5⋅56
Multiply 5 by 5.
x=256
x=256
x=256
The result can be shown in multiple forms.
Exact Form:
x=256
Decimal Form:
x=4.16‾
Mixed Number Form:
x=416
Solve for x -6/5x=-5   ## Download our App from the store

### Create a High Performed UI/UX Design from a Silicon Valley.  Scroll to top